Choque de competências e governança: estudo longitudional de dois grupos brasileiros de empresas de distribuição de energia elétrica - Geraldo Filho, Brasil (2007)
Various studies in the corporate strategy literature just proposed theories about how the core competencies are created and retained, influencing the superior performance of the organizations. However, the field still needs more empiric research. So, this study tries to explain the reasons why some subsidiaries of two Brazilian groups of electricity utilities work well and others do not, regarding the operational and financial results of the firms. Through the holding company perspective, the core competences, the commitment and the corporate governance structures are analyzed in order to find the influences they have over the subsidiary performance regarding the regulatory changes the electrical sector experienced. Using longitudinal case study methodology, the author has analysed the history of ELETROBRÁS group and REDE group in order to build a timeline perspective to guide the study. The results indicate that the environmental change has a clear influence over the core competences and the structures of corporate governance could influence the organizational performance. At the end, some recommendations and indications for further research are given.